Long-Term Variability of Precipitation form in Hornsund (Spitsbergen) in Relation to Atmospheric Circulation (1979–2009) - Łupikasza, Ewa (Bulletin of Geography. Physical Geography Series, 2010)
The paper discusses the impact of the atmospheric circulation on the long-term variability of liquid, mixed and solid precipitation. The three precipitation forms were characterised by their totals, the number of days when they prevailed, and the contribution of each to the overall precipitation totals. Trends, as a background to further analysis, were calculated with regard to each characteristic of each precipitation form. The most significant increases were recorded in the contribution of liquid precipitation to the overall precipitation totals in September and in the mixed precipitation totals in December and November. Arctic Oscillation (AO) was found to have only a minor influence on the long-term variability of precipitation characteristics. The AO phase could to some degree account for the observed variation in the number of days with liquid precipitation. On the other hand, the direction of the local advection could account for considerably more of this variability and also the variability in liquid precipitation totals.